1998
DOI: 10.1007/bf02467702
|View full text |Cite
|
Sign up to set email alerts
|

Electrically driven capillary size exclusion chromatography

Abstract: SummaryElectrically driven size exclusion chromatography (ED-SEC) of polystyrenes in packed capillaries using dimethylformamide as solvent is demonstrated. The efficiency and retention behaviour of polystyrenes under pressure and electro drive were investigated. Under pressure drive the plate height (H) increases steadily with increasing linear velocity (u) whereas under electro drive the H-u curves largely coincide and are very fiat. At higher velocities the plate heights are about 50 % smaller with electro d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 17 publications
(18 reference statements)
1
27
0
Order By: Relevance
“…Size-based separation mechanisms have not been fully exploited in CEC, excluding capillary gel electrophoresis, which relies on sieving rather than size exclusion [47]. The only true size exclusion-based separations in a pure CEC mode, for MW neutral polymers, were reported by Venema et al and Stol et al, using bare silica columns [48][49][50] and by our group using polymeric stationary phases [51]. Peters et al [52] had demonstrated the separation of polystyrene standards on a methacrylate-based monolithic column.…”
Section: Introductionmentioning
confidence: 99%
“…Size-based separation mechanisms have not been fully exploited in CEC, excluding capillary gel electrophoresis, which relies on sieving rather than size exclusion [47]. The only true size exclusion-based separations in a pure CEC mode, for MW neutral polymers, were reported by Venema et al and Stol et al, using bare silica columns [48][49][50] and by our group using polymeric stationary phases [51]. Peters et al [52] had demonstrated the separation of polystyrene standards on a methacrylate-based monolithic column.…”
Section: Introductionmentioning
confidence: 99%
“…, and zone electrophoresis of inorganic anions [7] and drugs (sometimes in a binary mixture with ,6% acetic acid) [8][9][10][11][12]. It has been used in chiral separations [13][14][15][16], in capillary electrochromatography of retinyl esters (in a mixture with 1% methanol) [17], in capillary size exclusion electrochromatography [18][19][20], in capillary gel electrophoresis of neutral polymers (mostly in mixtures with 1-6% water) [21], and in other applications [22][23][24][25][26]. Its influence on the electroosmotic flow (EOF) has been studied in both uncoated [7,[27][28][29][30] …”
mentioning
confidence: 99%
“…Figure 3 shows the van Deemter plot of a 2-mm-long SEEC column for FITC-insulin using either 50 or 10% ACN in the running buffer. This figure clearly shows that, at 10% ACN, the velocity is high enough for the mass transfer terms of the van Deemter equation to dominate [38], while these contributions are negligible at 50% ACN. Additionally, the high ACN content may reduce hydrophobic interactions, contributing to an overall decrease in H at 50% ACN.…”
Section: Seecmentioning
confidence: 91%
“…Pressure imbalances that arise from the difference in EOF between the open-channel segments and the packed column can disrupt flow patterns [33]. To reduce these imbalances and perform SEEC separation of proteins, charge needs to be introduced by dynamically modifying the beads with a charged surfactant [34][35][36][37][38]. Through the use of both neutral 0.01% Tween 20 to reduce nonspecific adsorption [2,39] and 0.25 mM (0.008%) SDS [40],] protein separation was possible, the currents were stable and the performance was reproducible.…”
Section: Seecmentioning
confidence: 99%